INTRUMENTATION FOR ADENOTONSILLECTOMY SURGERY - Bedaque, Henrique; Ferreira, Lidiane Maria de Brito Macedo; Júnior, José Diniz; Gibson, Deborah Carla Santos; Santos, Halan Araújo; Vasconcelos, Lucas Marinho (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Introduction: The successful surgical procedure depends on a set of processes and skills, among them the presence of the appropriate surgical instruments and a provision that brings ease and agility to the procedure are an important part of the surgical procedure. Objectives: The purpose of this article is to review the nomenclature of usual surgical instruments in adenotonsillectomy and to propose an instrument table organization to facilitate the exchange of instruments. Methods: Through images of real instruments individually and in their complex arrangement on the instrument table, the nomenclature and the arrangement of instruments and other materials for the organization of an efficient instrumentation table were explained in different stages. Conclusion: Knowledge about the nomenclature of surgical instruments and their proper organization for the surgery can be a facilitator for a successful surgery.